2021
DOI: 10.1002/adpr.202100143
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient White‐Light Emission Triggered by Sb3+ Dopant in Indium‐Based Double Perovskites

Abstract: Inorganic indium‐based halide double perovskites (DPs) are environmentally friendly alternatives to lead‐based halide perovskites in light‐emitting diodes, but commonly suffer from low quantum efficiency and harsh synthesis conditions. Herein, a large‐scale green method using water as solvent is developed for the synthesis of 3D Cs2NaInCl6 and 0D Cs2InCl5·H2O with/without Sb3+ dopant at room temperature. The transformation between Cs2InCl5·H2O and Cs2NaInCl6 products is controlled by the concentration of eco‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…The crystal structures of the three perovskite-related materials are shown in Figure 1, where Sb 26,43 The as-prepared Rb 3 InCl 6 :Sb 3+ , Cs 2 NaInCl 6 :Sb 3+ , and Cs 2 InCl 5 •H 2 O:Sb 3+ samples showed broadband green, blue, and yellow emission, respectively, and the profiles were consistent with previous reports. 23,42,43 The crystal structures of the obtained samples were characterized by powder X-ray diffraction (Figure S1). The X-ray diffraction patterns of all of the samples were in good agreement with the standard patterns.…”
Section: T H Isupporting
confidence: 87%
See 1 more Smart Citation
“…The crystal structures of the three perovskite-related materials are shown in Figure 1, where Sb 26,43 The as-prepared Rb 3 InCl 6 :Sb 3+ , Cs 2 NaInCl 6 :Sb 3+ , and Cs 2 InCl 5 •H 2 O:Sb 3+ samples showed broadband green, blue, and yellow emission, respectively, and the profiles were consistent with previous reports. 23,42,43 The crystal structures of the obtained samples were characterized by powder X-ray diffraction (Figure S1). The X-ray diffraction patterns of all of the samples were in good agreement with the standard patterns.…”
Section: T H Isupporting
confidence: 87%
“…The crystal structures of the three perovskite-related materials are shown in Figure , where Sb 3+ forms [SbCl 6 ] 3– octahedrons in three-dimensional Cs 2 NaInCl 6 and zero-dimensional Rb 3 InCl 6 , and [Sb­(H 2 O)­Cl 5 ] 2– octahedrons in zero-dimensional Cs 2 InCl 5 ·H 2 O. Samples of Rb 3 InCl 6 : Sb 3+ , Cs 2 NaInCl 6 : Sb 3+ , and Cs 2 InCl 5 ·H 2 O: Sb 3+ with a trace amount of the dopant (<0.1% atomic percentage) were synthesized by a previously reported solution method. , The as-prepared Rb 3 InCl 6 : Sb 3+ , Cs 2 NaInCl 6 : Sb 3+ , and Cs 2 InCl 5 ·H 2 O: Sb 3+ samples showed broadband green, blue, and yellow emission, respectively, and the profiles were consistent with previous reports. ,, The crystal structures of the obtained samples were characterized by powder X-ray diffraction (Figure S1). The X-ray diffraction patterns of all of the samples were in good agreement with the standard patterns.…”
mentioning
confidence: 99%
“…The yellow emission was also not from Cs 2 InCl 5 •H 2 O impurity or Cs 2 NaInCl 6 host (Figure S4). 40 Similar broadband LE emission centered at 570 nm was observed from Sb 3+ -doped Cs 2 NaInCl 6 , as shown in Figure 2b. It had a similar PLE spectrum to that of the Sb 3+ /Bi 3+ codoped sample for LE emission.…”
supporting
confidence: 74%
“…Facile precipitation was used to prepare Sb 3+ and Bi 3+codoped Cs 2 NaInCl 6 double perovskites, as reported in our previous work (details in Supporting Information). 40 By adjusting the feeding ratio between Sb 3+ and Bi 3+ precursors, a series of microcrystals with varied Sb 3+ and Bi 3+ content was obtained (Figure S2). When Sb 3+ and Bi 3+ were substituted in the In 3+ position, the product retained the Cs 2 NaInCl 6 structure, as demonstrated by powder X-ray diffraction data in Figure 1a.…”
mentioning
confidence: 99%
“…Low-dimensional lead (Pb)-free perovskite derivatives have been attracting increasing interest as environmentally friendly alternatives for use in light-emitting diodes (LEDs), X-ray detectors, photocatalysis, and so on because of their excellent material properties, such as high photoluminescence quantum yields (PLQYs), excellent solution processability, and tunable emission covering the full visible range. However, most of the metal halide materials exhibit a soft ionic lattice, leading to facile ion migration and/or transformation to undesired phases upon exposure to humidity, heat, and light. Among various kinds of environmental factors, humidity exerts a very important role in influencing material composition and thus their optical properties. For example, Chen et al reported that the green-emitting Cs 3 InCl 6 :Sb 3+ can be transformed into the orange-emitting Cs 2 InCl 5 ·H 2 O:Sb 3+ upon exposure to moisture .…”
mentioning
confidence: 99%